Molecular Cloning, Characterization and Expression in E. Coli of a cDNA Encoding the Growth Hormone in Rainbow Trout - Agellon, Benn Luis (My University, 1986)
RNA blot analysis, cell-free translation and protein immunoblot analyses were used to characterize mRNA purified from pituitary glands of rapidly growing rainbow trout. Cell-free translation products of total pituitary RNA, analyzed by direct immunoprecipitation or protein immunoblot analysis with an antiserum to chum salmon GH, indicated that the rainbow trout pre-GH is a polypeptide of 25 kDa. RNA blot analysis competitor, revealed the presence of at least four size classes of pituitary-specific RNA sequences. The abundant class of mRNA had a size immunoblot analysis, it was found that the GH mRNA size class. Furthermore, the size of the GH mRNA of rainbow trout is similar to that of mammalian GH mRNA.
The immunochemical reactivity of rainbow trout GH with antiserum to other GH was also determined. Results of this study indicate that antisera to mammalian GH crossreact poorly with rainbow trout GH. This observation correlates with the inability of any of the mammalian GH nucleic acid probe sequences to hybridize with a specific mRNA in the pituitary gland of rainbow trout. On the other hand, antiserum to chum salmon GH shows good crossreactivity with rainbow trout GH present in cell-free translation products programmed by rainbow trout pituitary RNA or in extracts of rainbow trout pituitary glands. Several attempts were made to construct a cDNA library using total pituitary RNA of rapidly growing rainbow trout. The early attempts were unsuccessful and reasons for the failures are discussed. Subsequently, a simplified method for the synthesis and cloning of cDNA was developed. A library containing approximately 30,000 recombinant clones was obtained following this procedure. A simple immuno-screening procedure using an antiserum to chum salmon GH as probe was also developed and serveral recombinant clones carrying the complimentary DNA sequence of rainbow trout GH mRNA were isolated. One clone, designated pAF51, was found to program the synthesis of an immunoreactive polypeptide of 24kDa and contains a cDNA insert of approximately 900bp. The cDNA sequence in pAF51 was determined by direct super-coiled plasmid sequencing. The cloned sequence encode, a hybrid polypeptide that includes the first 9 amino acid residues of the E. coli B-galactosidase a portion of the predicted signal peptide of the rainbow trout pre-GH and the entire sequence of the mature GH polypeptide. The primary structure of the mature GH polypeptide predicted from the rainbow trout GH cDNA sequence shows complete homology with the chum salmon GH and weak homology to the primary structures of the mammalian GH. The tertiary structure of the rainbow trout GH was also compared with other GH polypeptides. The pairwise comparisons of the hydropathy profiles of bovine, human, rat and rainbow trout GH polypeptides indicate that regions of similarity exist between the rainbow trout GH and the mammalian GH. In particular, there are two major regions of similarity found near the amino terminal and at the carboxyl terminal region. These regions correspond to hydrophilic domains of the GH molecules. The significance of these domains is discussed.
The biological activity of the rainbow trout GH synthesized in bacteria was tested in vivo. The chimeric hormone was partially purified from extracts of E. coli harboring plasmid pAF51. The hormone was administered to intact fingerling and yearling rainbow trout by intra-peritoneal injection, and to fry by the dip methoid. The results from the in vivo test indicate that the chimeric GH is biologically active with respect to its growth promoting activity; a marked enhancement of growth was seen in GH-treated fish. A dose of hormone as low as 0.2 ug/g of body weight when administered by injection of 50 ug/l GH when administered by dipping is sufficient to promote enchanced growth. However, high dosages used in this study consistently exhibited the least induction of growth, althought significantly higher than the controls. Certain morphological and behavioral effects were also observed. Analysis of compositiion of muscle tissue obtained from GH-treated and untreated fish indicated no detectable difference in tissue quality.
Keywords: Physical Sciences and Mathematics; Physical Sciences and Mathematics